ANALISIS COVERAGE JARINGAN WIRELESS UGM-HOTSPOT DI JURUSAN TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI UNIVERSITAS GADJAH MADA - , NUGRAHA TRIATMAJA; , Widyawan S.T., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
UGM One of the key technologies and a trend in computer network is a wireless computer network technology (Wireless Local Area Network / WLAN). This technology is the technology developments of the local computer network (Local Area Network) that enable efficiency in the implementation and development of computer networks because it can improve user mobility and given the limitations of computer network technology using the cable media. At the University of Gadjah Mada area used a wireless network that -Hotspot. UGM is a Captive Portal Hotspot Wireless Network using authentication Chillispot UGM which also has a login authentication using LDAP security UGM's in the PSDI email UGM. UGM- Hotspot is also an official SSID of the AP in the UGM. In application there are still many obstacles such as power range and the other AP collide channel. This study aims to design and optimize WLAN installations in the campus environment with the case in building the Department of Electrical Engineering and Information Technology University of Gadjah Mada. Stages in the course of this research consists of the preparation and measurement of signal data access point coverage in the field, the field of data processing, as well as the analysis and comparison of data. This study aimed to compare baseline coverage with coverage for conditions after the addition of a new access point. Research was also conducted to compare the throughput of TCP and UDP access on 2 conditions. The results showed the range of coverage after the addition of an access point. Additions to good signal coverage per floor on average an increase of 26.33%. Testing throughput at the same point on the 2 conditions also showed an increase in average and maximum throughput is obtained.